Evaluation of the Ocular Surface and Meibomian Gland in Obstructive Sleep Apnea Hypopnea Syndrome - Liu, Shaohua; Li, Shisheng; Li, Mengmeng; Zeng, Shiying; Chen, Baihua; Zhang, Liwei (Frontiers in Medicine, 2022)
Purpose: To assess the ocular surface and meibomian gland (MG) of patients with obstructive sleep apnea hypopnea syndrome (OSAHS) and to explore the effects of surgery for OSAHS on the ocular surface and MG. Methods: Based on the apnea hypopnea index (AHI), 21 patients with mild OSAHS (Group A, 5/h ≤ AHI < 15/h), 20 patients with moderate OSAHS (Group B, 15/h ≤ AHI <30/h), 62 patients with severe OSAHS (Group C, AHI ≥30/h) were examined. The ocular surface and MG were evaluated using Keratograph 5M. In addition, detailed Ophthalmic examination including visual acuity, refraction, slit-lamp examination of the anterior segment, corneal fluorescein staining (CFS), ocular surface disease index (OSDI) scoring, Schirmer Ⅰ test (SIT) and serum lipid measurement was performed. For OSAHS patients with dry eye syndrome (DES) who underwent uvulopalatopharyngoplasty for improving AHI, the conditions of the ocular surface and MG were compared before surgery and three months after surgery. Results: There were no significantly different in the OSDI score, tear meniscus height (TMH), or loss ratio of the lower eyelid (LRLE) among these groups. The first noninvasive tear film breakup time (fNIBUT), average noninvasive tear film breakup time(avNIBUT), bulbar redness index (BRI), lipid layer grading (LLG), CFS, plugged orifices and distortion in MG, the loss ratio of upper eyelid (LRUE), and the incidence of DES, floppy eyelid syndrome (FES) and meibomian gland dysfunction (MGD) showed significant differences between Groups A and C (p=0.015, p=0.018, p<0.001, p=0.022, p=0.036, p=0.007, p=0.019, p=0.017, p=0,045, p=0.013, and p=0.029, respectively). In the correlation analyses, the fNIBUT, avNIBUT, SIT and LLG had negative correlations with the AHI (p=0.013, p=0.010, p=0.003, p<0.001, and p=0.006, respectively). The BRI, CFS and LRUE were positively correlated with the AHI (p=0.006, p=0.007, and p=0.046, respectively). Three months after surgery, there were no significant differences in the ocular surface or MG. Conclusion: Patients with severe OSAHS have poor stability of tear film and are prone to lipid-deficient dry eye as a result of the loss of meibomian gland. By improving the AHI, the ocular surface damage of OSAHS patients cannot be reversed in a short time.